How Long Do Most Seizures Last? A Systematic Comparison of Seizures Recorded in the Epilepsy Monitoring Unit - Jenssen, Sigmund; Gracely, Edward J.; Sperling, Michael R. (Epilepsia (Copenhagen), 2006)
Purpose: More information is needed regarding how long seizures typically last, since this influences treatment decisions. Seizure type and other factors could influence seizure duration. Methods: Data were collected from a random sample of patients being evaluated with continuous video and scalp EEG. Seizure duration was defined as time from early sign of seizure (clinical or EEG) until the end of seizure on EEG. Seizures were categorized as simple partial (SPS), complex partial (CPS), secondarily generalized tonic–clonic (SGTCS), primary generalized tonic–clonic (PGTCS) and tonic (TS). SGTCS were divided into a complex partial part (SGTCS/CP) and a tonic–clonic part (SGTCS/TC). Median and longest duration of each seizure type in each individual were used. Comparisons of seizure types, first and last seizure, area of onset, and state of onset were performed. Results: Five hundred seventy‐nine seizures were recorded in 159 adult patients. Seizures with partial onset spreading to both hemispheres had the longest duration. SGTCS were unlikely to last more than 660 s, CPS more than 600 s, and SPS more than 240 s. PGTCS and TS had shorter durations, but the number of subjects with those two types was small. CPS did not differ in duration according to sleep state at onset nor side of origin. Conclusion: A working definition of status epilepticus in adults with cryptogenic or symptomatic epilepsy can be drawn from these data for purposes of future epidemiologic research. More information is needed for the idiopathic epilepsies and in children.